Calciphylaxis in POEMS syndrome: Case report - Danica Novacic; Thomas Uldrick; Alina Dulau-Florea; Colleen Evans Howe; Chyi-Chia R. Lee; Heidi H. Kong; William A. Gahl (Rare)
POEMS Syndrome is a constellation of findings including Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal plasma cell disorder, and Skin changes. Calciphylaxis, a microangiopathy involving vascular calcification and thrombotic occlusions, occurs rarely in POEMS. We present a case of prominent calciphylaxis that antedated the diagnosis of POEMS. The patient presented with extensive ecchymoses progressing to necrotic lesions in the setting of acute renal injury. Previously, she had chronic slowly progressive polyneuropathy, splenomegaly, hypothyroidism, amenorrhea, and ascites. Calciphylaxis was diagnosed on skin biopsy, and POEMS was diagnosed based upon clinical findings plus a bone marrow biopsy showing 15% lambda chain restricted plasma cells. Treatment for the calciphylaxis was supportive with fluids, tissue debridement, wound vacuum devices and antibiotics for secondary infection. Myeloma was treated with bortezomib and steroids. All aspects of the patient’s manifestations improved. We conclude that calciphylaxis can be a prominent feature of POEMS and can appear prior to recognition of the full-blown syndrome.